KEPEMIMPINAN TRANSFORMASIONAL DALAM KONTEKS PENDIDIKAN ISLAM DI ERA DISRUPSI - Ramadina, Evy; Aziz, Abd.; Efendi, Nur (As-Sulthan Journal of Education, 2025)
Islamic Educational Institutions (LPI) in Indonesia play a strategic role in shaping a generation of faithful, knowledgeable, and virtuous Muslims. However, in the era of globalization and digitalization, LPI faces multidimensional challenges such as human resource quality, leadership issues, and adaptation to technological advances. This study aims to analyze the implementation of transformational leadership in the context of Islamic education as a strategy to drive sustainable institutional transformation. The method used is a literature study with a qualitative analysis of the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The results show that transformational leadership, based on Islamic values ​​such as uswatun hasanah and fastabiqul khairat, plays a significant role in improving academic quality, building Islamic character, and strengthening institutional adaptation to technology and globalization. Effective leadership is characterized by four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individual attention. Furthermore, the transformation of leadership intelligence—including intellectual, emotional, spiritual, cultural, and digital intelligence—is key to strengthening LPI's competitiveness in the era of disruption. The research findings confirm that the success of the transformation of Islamic educational institutions is largely determined by a leadership mindset that is oriented towards responsibility, service, and trust, rather than power and honor.